PENANAMAN PENDIDIKAN KARAKTER DI SMP NEGERI 10 SAMPIT - Mahmuddin Mahmuddin; Siti Halimah; Nurma Yunita (STKIP MUHAMMADIYAH SAMPIT, 2020)
Character education make the best preparation for the better student’s personality in his or her life. The study is done to find out how to invest a character education in SMP Negeri 10 Sampit. The subject in this study is a total SMP Negeri 10 Sampit totaling 202 students. The method of data collection used is interviews and observations. The study shows that there are fourteen character values found in the behavior of SMP Negeri 10 Sampit.